Congenital rubella syndrome: a case report - Osman, Mahmoud M.; Zakaria, Meryat T.; Alnofal, Mutassem F.; Hamdoun, Sulafa A.; Alissa, Mohammed S. (International Journal of Contemporary Pediatrics, 2020)
Currently, rubella virus infections are very rare in many countries, and may not be recognized promptly. However, congenital rubella syndrome still appears, often in infants of mothers coming from countries with suboptimal vaccination programs. We describe a case of CRS in a full-term baby girl born to a foreign mother who documented perinatal antibodies against rubella. The baby had the classical abnormalities seen in infants with CRS include congenital cardiac and ocular anomalies. The diagnosis was confirmed by positive rubella serology in both infant and mother. Vaccination is the only known prophylactic measure for congenital rubella syndrome.